LAMBERT-EATON MYASTHENIC SYNDROME IN A TERTIARY NEUROLOGY CENTRE. Issue 12 (15th November 2016) - Ellul, Mark; Bonello, Michael; Wieshmann, Udo
Abstract : Introduction: Lambert-Eaton myasthenic syndrome (LEMS) is a rare but well-characterised neuromuscular disorder. 50–60% of cases are associated with small cell lung cancer (SCLC). The Dutch-English LEMS tumour association prediction (DELTA-P) score was developed to guide malignancy screening in LEMS. Aim: To review the clinical features, investigations, management and clinical course of LEMS patients at the Walton Centre over a 20 year period. Methods: Using pharmacy records, we identified LEMS patients treated with 3, 4-diaminopyridine (3, 4-DAP). We then reviewed medical records, imaging and laboratory results. Results: Of 16 patients analysed, 8 had SCLC and one had thymoma. All had lower limb weakness at presentation. DELTA-P score discriminated between SCLC-LEMS and NT-LEMS (p=0.04), as did smoking history (p=0.03). Bulbar symptoms, autonomic symptoms, age at onset and weight loss alone did not discriminate between SCLC-LEMS and NT-LEMS. Most cancers were diagnosed on the initial computed tomography (CT) or positron emission tomography (PET)-CT. Most patients responded to treatment with either 3, 4-DAP, intravenous immunoglobulin or steroids. Conclusions: Our survey confirms that the DELTA-P score is a useful clinical tool to stratify screening for malignancy in patients with LEMS, but suggests that isolated clinical features, such as bulbar or autonomic symptoms, are not necessarily indicative of SCLC-LEMS.